The Impact of Price, Product Quality, and Brand Image on Consumer Purchase Decisions of Wardah Cosmetics Skincare Products : (A Study on Students of the Entrepreneurship Program at the Muhammadiyah Sumatera Institute of Technology) - Anggraini, Rafikha; Khasanah, Siti Fatimatul; Rama, Kris Suspon (The Eastasouth Management and Business, 2025)
Currently, various skincare brands, both well-know and less recognized, have emerged and are widely available in many places. These brands continue to innovate to meet consumer’s needs and desires. Consumers now have greater freedom in choosing skincare products due to the wide variety of options offered. Consequently, consumers now have a wider range of options in terms of price, product quality, and brand image to meet their preferences. This study seeks to examine the impact of price, product quality, and brand image on purchase decisions. An explanatory approach is employed, utilizing a non-probability sampling method. A total 100 respondents, consisting of those who have purchased, plan to purchase, or are aware of the existence of Wardah Cosmetics, participated in this study. Data was collected online through questionnaires distributed via Google Forms on social media platforms. The data analysis was performed using SPSS 26 for Windows. The study results reveal that price, product quality, and brand image collectively have a significant impact on purchasing decisions. Individually, price has a positive and significant influence on purchasing decision. Similarly, product quality positively and significantly affects purchasing decisions, as does brand image, which also shows a positive and significant effect.